2022
DOI: 10.1177/23259582221121448
|View full text |Cite
|
Sign up to set email alerts
|

Not a Problem at All or Excluded by Oneself, Doctors and the Law? Healthcare Workers’ Perspectives on Access to HIV-Related Healthcare among Same-Sex Attracted Men in Tanzania

Abstract: Background: An increasing body of literature focuses on access to healthcare services for men who engage in sex with other men in Africa, but how healthcare workers conceive of this topic of healthcare workers’ views on men's care has not been much studied. Drawing on qualitative research, this article explores healthcare providers’ perspectives on access to HIV-related healthcare services among gender and sexuality diverse men in Tanzania. Methods: A qualitative study was conducted among healthcare workers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, Seretlo and Mokgatle [14] found that some primary healthcare (PHC) nurses had a judgmental attitude and were surprised that there were queer patients, associating their sexuality with childhood traumas, whilst other PHC nurses were not judgmental and were willing to serve patients despite their sexuality. Additionally, a Tanzanian study found that certain HCPs actively helped to limiting access to healthcare for men of varied genders and sexualities [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, Seretlo and Mokgatle [14] found that some primary healthcare (PHC) nurses had a judgmental attitude and were surprised that there were queer patients, associating their sexuality with childhood traumas, whilst other PHC nurses were not judgmental and were willing to serve patients despite their sexuality. Additionally, a Tanzanian study found that certain HCPs actively helped to limiting access to healthcare for men of varied genders and sexualities [29].…”
Section: Discussionmentioning
confidence: 99%